Clinical impact of colonization with multidrug‐resistant organisms on outcome after allogeneic stem cell transplantation in patients with acute myeloid leukemia. Issue 2 (28th September 2017) - Scheich, Sebastian; Lindner, Sarah; Koenig, Rosalie; Reinheimer, Claudia; Wichelhaus, Thomas A.; Hogardt, Michael; Besier, Silke; Kempf, Volkhard A. J.; Kessel, Johanna; Martin, Hans; Wilke, Anne C.; Serve, Hubert; et al.
Abstract : BACKGROUND: Allogeneic hematopoietic stem cell transplantation (allo‐HSCT) is a curative treatment option for patients with acute myeloid leukemia (AML). During transplantation, patients undergo a period of severe neutropenia, which puts them at high risk for infectious complications. However, the impact of patient colonization with multidrug‐resistant organisms (MDRO) on overall survival remains unclear. METHODS: In this retrospective, single‐center study, the authors analyzed data from 264 patients with AML who underwent a first allo‐HSCT between January 2006 and March 2016 at their institution. Primary endpoints were overall survival and nonrelapse‐related mortality. RESULTS: One hundred forty‐two of 264 patients (53.8%) were colonized by at least 1 MDRO, mainly with vancomycin‐resistant Enterococcus faecalis / faecium (n = 122). The characteristics of colonized patients did not differ from those of MDRO‐negative patients with respect to median age (53.5 vs 53 years), cytogenetic risk according to European LeukemiaNet criteria, remission status before allo‐HSCT (first or second complete remission: 55.7% vs 60.7%, respectively; active disease: 44.4% vs 39.3%, respectively), donor type, or hematopoietic cell transplantation‐comorbidity index (HCT‐CI). Compared with noncolonized patients, MDRO‐positive patients had an inferior probability of survival at 5 years (43.3% vs 65.5%; P = .002), primarily because of a higher cumulative incidence of nonrelapse‐related mortality (33.9% vs 9.4%; P < .001). Death caused by infections occurred in 15.5% of colonized patients versus 4.9% of noncolonized patients. There was no difference in the cumulative incidence of relapse in MDRO‐positive versus MDRO‐negative patients (33.8% vs 42.1%, respectively; P = .798). CONCLUSIONS: The current data emphasize the importance of regular MDRO screenings and prompt further investigations into the impact of colonization with MDRO on the immune system after allo‐HSCT. Cancer 2018;124:286‐96 . © 2017 American Cancer Society . Abstract : Patients who are colonized by multidrug‐resistant organisms have lower survival because of higher nonrelapse‐related mortality after allogeneic hematopoietic stem cell transplantation. Mortality during severe neutropenia after transplantation does not differ between patients with and without colonization, but the period as an outpatient after transplantation seems to be most critical for fatal outcomes in colonized patients.